Dose-dense chemotherapy with weekly paclitaxel and 3-weekly carboplatin for recurrent ovarian cancer - Wei-Chun Chen; Huei-Jean Huang; Ting-Chang Chang; Hung-Hsueh Chou (Elsevier, 2020)
Objective: To analyze the response to dose-dense chemotherapy of weekly paclitaxel and 3-weekly carboplatin in recurrent ovarian cancer, and to report results of literature review. Materials and methods: Patients accepted weekly paclitaxel 80 mg/m2 on day 1, 8, 15 and carboplatin on day1 at area under curve (AUC) 6 every 21 days were reviewed for the response rate, progression-free survival, overall survival, and toxicity during January 2012 to April 2016 in Chang Gung Memorial Hospital at Linkou, Taiwan. Results: Sixteen patients with recurrent ovarian cancer, including 1 platinum-resistant, 7 partially platinum-sensitive, and 8 platinum-sensitive, accepted a median of 6 cycles of chemotherapy (range 3-10). The overall response rate (ORR) and complete response (CR) rate were 93.8%, and 62.5%, respectively. The median PFS of all patients were 10.9 months (range 4.3-40.5). The median time to response (TTR) was 29.0 days (range 19.6-38.4). The median disease-free survival (DFS) after CR was 5.6 months (range 1.2-34.2). Grade 3 at least toxicity included anemia (6.3%), neutropenia (50%), and thrombocytopenia (18.8%).Twenty-nine articles on phase I, II, III, or retrospective studies of dose-dense chemotherapy with weekly paclitaxel were reviewed. Conclusion: This is the first report using Japanese Gynecologic Oncology Group 3016 protocol, weekly paclitaxel and 3-weely carboplatin, on recurrent ovarian cancer. The current study showed high ORR and CR with tolerable toxicities. Our study suggested dose-dense chemotherapy with paclitaxel, especially combining carboplatin created high efficacy probably by anti-angiogenesis. However, consolidation or maintenance therapy is needed to prolong DFS. Keywords: Dose-dense chemotherapy, Metronomic chemotherapy, Weekly paclitaxel, Carboplatin, Recurrent ovarian cancer